2007
DOI: 10.1080/10781910701471306
|View full text |Cite
|
Sign up to set email alerts
|

Former Lord's Resistance Army child soldier abductees: Explorations of identity in reintegration and reconciliation.

Abstract: This article explores the reintegration experiences of former Lord's Resistance Army (LRA) child abductees into Acholi society in Northern Uganda. Based on interviews with 10 former abductees who were returned to communities for 2 years or more, it explores identity transitions for youth from pre-abduction, to their forced abduction into the LRA and subsequent escape and reintegration. Returnees such as those who have been members of the LRA for a long time, or who have been implicated in the commission of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…She did not trust or feel a part of the group, yet felt alienated from those outside the group. Like the abducted children in Uganda who were forced to attack members of their community or those in similar communities (Veale & Stavrou, 2007), she developed identity conflicts. Her male counterpart, who had been forcibly recruited by the guerrillas, had much interaction with others guerrilla fighters and began to identify with the FMLN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She did not trust or feel a part of the group, yet felt alienated from those outside the group. Like the abducted children in Uganda who were forced to attack members of their community or those in similar communities (Veale & Stavrou, 2007), she developed identity conflicts. Her male counterpart, who had been forcibly recruited by the guerrillas, had much interaction with others guerrilla fighters and began to identify with the FMLN.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers used a socio-cultural model, where identity was formed through participation in an organized space called ''communities of practice'' where mature practitioners passed on knowledge and practice to novices practitioners (Veale & Stavrou, 2007). After being abducted, children resisted absorbing the identity of the rebel group but had a great deal of conflict when they went from abductees to soldiers.…”
Section: Combatants and Identity Issuesmentioning
confidence: 99%
“…Community members described returned children and young people who had been through psychosocial reintegration programmes as 'less rude' and as 'having more respect for people and elders' (Veale and Stavrou 2007). In northern Uganda this programming has tended to depoliticise the position of children and call for a focus on child rights and welfare.…”
Section: The Psychological and The Political Childmentioning
confidence: 99%
“…In Uganda, former child-soldier abductees reported that they were welcomed back, as people saw that they were victims who had been taken against their will; however, if they got angry or aggressive for any reason, they experienced a shift from being identified as a friend or peer to identification as a 'rebel' (Veale and Stavrou 2007). In international discourse, and increasingly within international law, former child soldiers are considered primarily as victims of conflict (Coˆ te´ 2005: 4).…”
Section: Re-politicising Child Forced Migration: An Exploration Of DImentioning
confidence: 99%
“…Veale and Stavrou (2007) for instance, have explored the issue of changing identities of child soldiers due to abduction and its effect on reintegration. Other scholars like, Dickson-Gómez (2002), Berkowitz (1993), and Bandura (1973) have examined how social learning processes influence the mental and behavior changes that a child undergoes in the context of war.…”
Section: Introductionmentioning
confidence: 99%